Assesment of Thermal Comfort Dymamics in Central Java Province Using Era 5 Reanalysis Data - Alma Nugrahaning Putri; Purnomo Adi Saputro (CV. Era Digital Nusantara, 2026)
Central Java experiences high population density and increasing anthropogenic activities that potentially alter microclimatic conditions and decrease human thermal comfort. This study analyzes the spatial and temporal variations of thermal conditions across the province during 2017–2025. Air temperature and relative humidity data were obtained from the ERA5-Land reanalysis dataset and processed using Google Earth Engine. Thermal conditions were evaluated using the Discomfort Index (DI), while validation was carried out through comparison with in-situ observations from the Badan Pusat Statistika (BPS). The findings reveal a gradual increase in DI throughout the study period, indicating a decline in environmental comfort levels. Temporally, January recorded the highest DI due to elevated humidity, whereas October showed relatively more comfortable conditions. Spatial analysis demonstrates that highland regions consistently experienced lower DI compared to lowland and coastal areas, emphasizing the important role of elevation in shaping thermal conditions. Validation results confirm that ERA5-Land data are reliable for examining thermal comfort patterns in Central Java.